Assessment of Seismic Vulnerability for a Hospital Building Using Field Data and Various Numerical Analyses Considering Bidirectional Ground Motion Effects - Alireza Kharazian; Arianna Guardiola-Villora; Juan José Galiana-Merino; Sergio Molina; Gonzalo Ortuño-Sáez; Juan Luís Soler-Llorens; José Antonio Huesca-Tortosa; Igor Gómez; David Montiel-López (Applied Sciences)
For the assessment of seismic effects on RC buildings, the real structural condition has to be modelled as accurately as possible. Medical facilities and hospitals have to resist seismic actions and remain operational after seismic events. For this reason, a detailed seismic vulnerability assessment of a hospital building located in Orihuela, Spain, is presented in this paper using a combination of field monitoring data and numerical analysis. Ambient noise measurements from field monitoring using Raspberry Shake-based sensors are used to capture dynamic characteristics that describe the building behaviour. Data from these sensors were used to update and refine the finite element model of the structure for a detailed analysis of the building’s seismic performance. The different analytical procedures included both elastic and inelastic modelling, as well as static and dynamic assessments, to provide an exhaustive evaluation of the building’s behaviour under seismic loads. In the numerical model, the effect of masonry infill walls is considered, taking into account detailed material properties and structural configurations. Furthermore, the study carefully selects ground motion records representing two limit states—Damage Limitation (DL) and Severe Damage (SD)—to conduct an extensive seismic analysis. In each limit state applied to the structure, there are 14 bidirectional ground motions with components alternately directed along the two principal directions of the building. This analysis evaluated the structural response, focusing on torsional effects, inter-storey drift ratios, and the seismic performance of individual components. The results were compared to other analysis types, considering both overall and localised behaviour, to determine the reliability of different approaches. The findings support the idea that field monitoring data should be combined with advanced modelling techniques to achieve a more accurate evaluation of the building’s seismic vulnerability, considering bidirectional effects.